(untitled) (Eurasian Journal of Ecology, 2024)
There is currently a global increase in interest in the use of natural therapeutic muds.Therapeutic mud is a natural product that has a beneficial therapeutic effect on the skin and a lower incidence of adverse effects on the human body. The object of the study was water from two wells and a medicinal swamp in the settlement of Zhanakorgan district of Kyzylorda region. The present study examined the species composition of microalgae and cyanobacteria in two wells and in therapeutic swamps within the settlement of Zhanakorgan district. The objective of this study was to examine the species diversity, morphological and cultural characteristics of cyanobacteria, green and diatom algae in the Zhanakorgan district settlement, and to introduce them into axenic cultures for storage in a collection for potential utilization in industrial biotechnology, in the pharmaceutics, as well as in textile and food industry due to their rich chemical composition. The study yielded seven new axenic cultures of cyanobacteria, green algae, and diatoms, which were identified as Dunaliella salina, Chlamydomonas sp., Scenedesmus sp., Trichormus variabilis, Calothrix epiphytica, Nostoc oryzae, Navicula sp. Key words: therapeutic mud, microalgae, cyanobacteria, isolation, axenic cultures, morphological properties